Production of Two Proteins Encoded by the Bacteroides Mobilizable Transposon NBU1 Correlates with Time-Dependent Accumulation of the Excised NBU1 Circular Form - Wang, Jun (American Society for Microbiology, 2001)
NBU1 is a mobilizable transposon that excises from the Bacteroides chromosome to form a double-stranded circular transfer intermediate. Excision is triggered by exposure of the bacteria to tetracycline. Accordingly, we expected that the expression of NBU1 genes would be induced by tetracycline. To test this hypothesis, antibodies that recognized two NBU1-encoded proteins, PrmN1 and MobN1, were used to monitor production of these proteins. PrmN1 is essential for excision, and MobN1 is essential for transfer of the excised circular form. At first, expression of the genes encoding these two proteins appeared to be regulated by tetracycline, because the proteins were detectable on Western blots only after the cells were exposed to tetracycline. However, when the prmN1 gene and/or the mobN1 gene was cloned on a multicopy plasmid, production of the protein was constitutive. Initially, we assumed that the constitutive expression was due to loss of a repressor protein that was encoded by one of the other genes on NBU1. Deletions or insertions in the other genes (orf2 and orf3) on NBU1 and various integrated NBU1 derivatives abolished production of PrmN1 and MobN1. This is the opposite of what should have happened if one or both of these genes encoded a repressor. A second possibility was that when NBU1 excised, it replicated transiently, increasing the gene dosage of prmN1 and mobN1 and thereby producing enough PrmN1 and MobN1 for these proteins to become detectable. In fact, after the cells entered late exponential phase the copy number of NBU1 increased to 2 to 3 copies per cell. Production of PrmN1 and MobN1 showed a similar pattern. Any mutation in NBU1 that decreased or prevented excision also prevented elevated production of these two proteins. Our results show that the apparent tetracycline dependence of the production of PrmN1 and MobN1 is due to a growth phase- or time-dependent increase in the number of copies of the NBU1 circular form.